Acute 2,4-dichlorophenoxyacetic acid intoxication in broiler chicks - Morgulis, M. S. F. A.; Oliveira, G. H. [UNESP]; Dagli, M. L. Z.; Palermo-Neto, J. (Poultry Science Assoc Inc, 1998)
The acute toxicity of 2,4-dichlorophenoxyacetic acid (2,4-D), a herbicide, was studied in chicks dosed with 100, 300, 500, or 600 mg 2,4-D/kg BW, by the oral route. Clinical, laboratory, and histopathological methods were used as indicators of toxicity. After acute exposure, the herbicide decreased motor activity and induced muscular weakness and motor incoordination; decreased weight gain; increased serum creatine kinase (CK) and alkaline phosphatase (AP) activities and serum uric acid (UA), creatinine (CR), and total proteins (TP) levels; and did not change serum aspartate aminotransferase (AST) or alanine aminotransferase (ALT) activities. These changes were time-and dose-dependent and reversible. The LD50 (lethal dose 50%) calculated for oral 2,4-D in chicks was 420 mg/kg BW (385 to 483). Chromatographic analysis of the serum of the intoxicated chicks showed the presence of the herbicide; the amount found was dose-and time-dependent, increasing from 2 to 8 h after exposure and decreasing afterwards. Histopathological post-mortem studies conducted on intoxicated chicks showed hepatic (vacuolar degeneration of the hepatocytes), renal (tubular nephrosis), and intestinal (hemorragic) lesions. Taken together, the observed alterations mainly reflected kidney and muscle tissue damage, although hepatic toxicity may also have occurred after acute 2,4-D intoxication.
Keywords: 2,4-dichlorophenoxyacetic acid; herbicide; intoxication; broiler; pesticide